Does one shot work? The acute impact of a single taurine dose on exercise performance: A meta-analytic review - Deng, H.; Song, T.; Yin, M.; Xu, K.; Zhong, Y.; Liu, P.; Sun, S.; Naharudin, M. N. B.; Yusof, A.; Fan, X. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This systematic review and meta-analysis evaluated the acute effects of a single dose of taurine supplementation on exercise performance and examined potential moderators related to participant characteristics, exercise modality, dosing, and administration protocols. Six electronic databases were searched up to July 2025, identifying 23 eligible randomized trials (k = 69, N = 308). A three-level random-effects meta-analysis indicated that acute taurine ingestion may be associated with small-to-moderate improvements in overall performance (g = 0.25, 95% CI [0.10, 0.39], I2 = 61%). Moderator analyses suggested that benefits were more apparent in males and across aerobic endurance, strength/power, and agility/coordination tasks, whereas evidence for anaerobic capacity and muscular endurance remained inconsistent. No significant dose-response relationship was detected within the commonly used 1-6 g range, suggesting potential threshold effects rather than linear trends. Both capsule and beverage formulations appeared effective, and nonlinear meta-regression indicated that ingestion about 1 h before exercise might yield the most favorable outcomes, although this timing effect was not robust in sensitivity analyses. Further analyses showed that several subgroup effects were attenuated after excluding influential studies, and prediction intervals frequently included the null, reflecting uncertainty in replicability. The overall certainty of evidence, assessed using GRADE, was rated low to very low due to heterogeneity, imprecision, and risk of bias. Collectively, these findings suggest that acute single-dose taurine supplementation holds promise as an ergogenic aid, but its effectiveness likely varies depending on dosage, blinding procedures, and exercise context. Additional high-quality trials are needed to establish more definitive recommendations.